ATTRACTING LIBRARIES TO THE LIBRARY ON THE BASIS OF CURRENT MODERN TECHNOLOGIES IN THE INFORMATION LIBRARY CENTER (Modern education and development, 2025)
This article analyzes modern innovations such as the creation of electronic libraries, the process of digitization, the use of multimedia technologies, improving library services through mobile applications and interactive services. It also examines the role of social networks and online marketing in attracting users to libraries, the impact of technology on attracting young people to libraries, and the importance of integration with global information systems. The article presents important steps and approaches for libraries to attract readers through the use of modern technologies.